2008
DOI: 10.1016/j.immuni.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Interleukin-22 Protects Mice from Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disease thought to be mediated by dysfunctional innate and/or adaptive immunity. This aberrant immune response leads to the secretion of harmful cytokines that destroy the epithelium of the gastrointestinal tract leading to further inflammation. IL-22 is a Th17 T cell associated cytokine that is bi-functional with both pro-inflammatory and protective effects on tissues depending on the inflammatory context. We show herein that IL-22 protects mice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
655
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(686 citation statements)
references
References 46 publications
27
655
2
2
Order By: Relevance
“…In addition, we identified a trend to fewer uNK cells in the decidua of patients with unexplained RPL compared to patients with a normal Research has shown that IL-22 can help constrain inflammation and protect mucosal sites, and that lower levels of IL-22 are associated with several inflammatory diseases, such as inflammatory bowel disease and acute graft-versus-host disease [18,19]. Additionally, it has been shown that, patients with worse symptoms and a prolonged disease course have significantly lower levels of IL-22 expression [18,19]. In this context, IL-22 likely plays a key role in maintaining decidual homeostasis and helps to constrain the inflammation common in early pregnancy.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, we identified a trend to fewer uNK cells in the decidua of patients with unexplained RPL compared to patients with a normal Research has shown that IL-22 can help constrain inflammation and protect mucosal sites, and that lower levels of IL-22 are associated with several inflammatory diseases, such as inflammatory bowel disease and acute graft-versus-host disease [18,19]. Additionally, it has been shown that, patients with worse symptoms and a prolonged disease course have significantly lower levels of IL-22 expression [18,19]. In this context, IL-22 likely plays a key role in maintaining decidual homeostasis and helps to constrain the inflammation common in early pregnancy.…”
Section: Resultsmentioning
confidence: 89%
“…ILC3s are a group of lymphocytes without T‐cell‐specific antigen receptors with particular accumulation at mucosal sites and serve as key regulators during intestinal inflammation 18, 19, 20, 21. ILC3s can rapidly respond to external stimuli and play critical roles in host defense, the resolution of inflammation and initiation of tissue repair in the gut 21, 22, 23, 24, 25, 26. These protective effects of ILC3s are mostly dependent on their production of the reparative cytokine IL‐22.…”
Section: Introductionmentioning
confidence: 99%
“…These protective effects of ILC3s are mostly dependent on their production of the reparative cytokine IL‐22. By binding to its receptor on epithelial cells, IL‐22 contributes to production of antimicrobial peptides and mucins, regulation of gut microbiota, maintenance of the gut barrier function and amelioration of intestinal inflammation 25, 26. But it remains unclear how ILC3s are activated and regulated during intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory/pathological nature is apparent in mouse models with diseases such as psoriasis [4] and rheumatoid arthritis [22], and T. gondii infection [11]. In contrast, IL-22 plays protective roles and has tissue-protective and antimicrobial properties in several mouse models with diseases such as inflammatory bowel disease (IBD) [23], hepatitis [24] and infection with invading pathogenic bacteria [10,25,26].…”
Section: Introductionmentioning
confidence: 99%